A Web-Based Medical Diagnostic System using Data Mining Technique - Muangprathub, Jirapond; Jareonsuk, Yutthaya; Sealiw, Aekarat (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
The purpose of this paper is to apply data mining technique for medical diagnostic system on web application supporting Thai language. This web would help users to reduce expense and time of visiting doctors. It is capable of giving preliminary diagnosis. The proposed system will discover the implication knowledge with association rules derived from formal concept analysis (FCA) to advice co-symptom of diagnosing to achieve more correctly. The association rules are built from its subconcept and superconcept relation from concept lattice. In addition, the proposed system supporting Thai language is challenged because this language is streaming string without the boundary delimiters. The proposed system is developed based on online web application to demonstrate real situation. The result show that the proposed system can suggest co-symptom to achieve more correctness for medical diagnostic